The Effect of Super Coach Change Projects on the Quality of Education and Training at the Center for the Development of Quality Assurance in Vocational Education in the Fields of Business and Tourism : A Narrative-Systematic Literature Review: Pengaruh Proyek Perubahan Super Coach terhadap Kualitas Pendidikan dan Pelatihan di Pusat Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Bisnis dan Pariwisata : Tinjauan Pustaka Naratif-Sistematis - Ham Idris Tumenggung Sis; Hapzi Ali (Jurnal Bisnis dan Ekonomi, 2026)
The change project is a core instrument in the leadership training of the State Civil Apparatus (ASN) which requires participants to design and implement real innovations in their work units. The success of a change project is largely determined by the quality of coaching mentoring, and in its development a number of educational institutions have developed a layered mentoring model known as "Super Coach". This article aims to synthesize the current literature on the relationship between Super Coach-based change projects and quality factors of education and training (diklat), as well as build a conceptual framework that is relevant to the context of the Center for the Development of Vocational Education Quality Assurance (BBPPMPV) in the Business and Tourism Sector. The method used is a narrative-systematic literature review with the principle of reporting transparency referring to PRISMA 2020, tracing sources from Scopus Q1/Q2, SINTA 1, and SINTA 2 indexed journals, as well as official regulatory documents. The results of the synthesis show that the effectiveness of executive coaching is determined by the characteristics of the coach, the characteristics of the coachee, the quality of the mentoring relationship, the coaching approach, organizational support, and the use of digital technology, while the quality of the training can be captured through the framework of the four levels of Kirkpatrick and the SERVQUAL dimension. This article proposes a conceptual framework that positions Super Coach-based change projects as an antecedence, learning transfer and leadership self-efficacy as intermediate variables, organizational support and digitalization as moderation, and training quality as outcome variables, along with three propositions that can be empirically tested in follow-up research.